The Mirror Neuron of Agapi (Love) and Trauma in Psychotherapeutic Groups and the contribution of the Forgiving Process - Catherine Mela (Forum for Group Psychotherapies and Processes)
From the beginning of life, a complex immune-biochemical dialogue is established in the brain, influenced by maternal experiences and the Social Unconscious. Trauma leaves traces in memory, either by its explicit or implicit transcription, psychologically experienced either as a conscious event or as an unconscious, blind and violent disorder, especially when the traumatic quantity overwhelms the Psychic Apparatus. The group factors interacting among different countries and cultures will be explored in relation to trauma‘s treatment and transformation in the group. Trauma‘s maintenance and transformation through generations, creates wounds in time, space, boundaries, transgenerationally influencing our genetic, ethical and national heritage. Psychotherapeutic factors like Agapi (Love), acceptance, containing, holding, gratitude, equal human-rights, transcultural and trans-religious-dialogue, corrective emotional experience and forgiving process are group parameters with impact in trauma’s healing after alteration of the Brain Plasticity. The forgiving process served as a marker in the evaluation of trauma‘s transformation by investigating the relationship between forgiveness, likelihood forgiveness and transgression related interpersonal motivations using Pearson’s correlation coefficient.